Meaning and transcendence of formative assessment: challenges of evaluation in Regular Basic Education - Luján-Mamani, Catherin (2022)
This article seeks to reflect on the meaning and transcendence of formative assessment and the main challenges of assessment practices in Regular Basic Education (EBR by its Spanish initials). A paradigm shift is required that stops peddling traditional teaching and an result-focused culture of evaluation. The documentary analysis of various sources that involved heuristics and hermeneutics of the state of the art made it possible to review representative regulations of global and local educational policy, as well as contemporary and recent research contributions of some significant fundamentals of general and substantive theory. It highlights that in Peru there are several regulations to implement this approach. However, this would not have an impact on international evaluations or on teachers’ pedagogical practice. Likewise, there are still several challenges regarding the development of a culture of evaluation requiring to stop conceiving it as a threat. Teachers are the key factor to achieve an effective implementation of formative assessment, but they need to be recognized in their professional role and consolidate a reflective practice that contributes to the change and transformation process in their pedagogical practice.